2018
DOI: 10.1101/404475
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TP53mutations and drug sensitivity in acute myeloid leukaemia cells with acquired MDM2 inhibitor resistance

Abstract: Background:MDM2 inhibitors are under investigation for the treatment of acute myeloid leukaemia (AML) patients in phase III clinical trials. To study resistance formation to MDM2 inhibitors in AML cells, we here established 45 sub-lines of the AML TP53 wild-type cell lines MV4-11 (15 sub-lines), OCI-AML-2 (10 sub-lines), OCI-AML-3 (12 sub-lines), and SIG-M5 (8 sub-lines) with resistance to the MDM2 inhibitor nutlin-3.Methods: Nutlin-3-resistant sub-lines were established by continuous exposure to stepwise incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 57 publications
2
10
0
Order By: Relevance
“…For instance, the absence of the der(4) in the B‐1 cell line, which is however present in MV‐4‐11, RS4;11, AN4;11, and SEM, suggests that it is the der(11) to detain a pivotal role in the promotion and maintenance of the malignancy . Differences in other molecular features, such as mutations of known cancer‐related genes TP53 and FLT3 , can prove useful in investigating the role of point mutations in leukaemogenesis (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the absence of the der(4) in the B‐1 cell line, which is however present in MV‐4‐11, RS4;11, AN4;11, and SEM, suggests that it is the der(11) to detain a pivotal role in the promotion and maintenance of the malignancy . Differences in other molecular features, such as mutations of known cancer‐related genes TP53 and FLT3 , can prove useful in investigating the role of point mutations in leukaemogenesis (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…The purification of DNA template was performed in the thermocycler (Eppendorf, German) according to the conditions indicated in Table (3).…”
Section: Protocol Of Pcr Production Cleanup With Exosapmentioning
confidence: 99%
“…Choosing the type of causative mutation of AML, helps decide treatment type . A previous study (3) investigated genes and DNA errors associated with TP 53 mutations and found that (hub genes) are responsible for it which are : LEP,BMP 2 , ITGA 2 B,MNX 1 , TRH,NMU,CDH 1 , KDR, CASR and APOE. These genes may change the type of treatment received by patient and may increase his healing opportunity.…”
Section: Introduction Tp53 and Correlations With Amlmentioning
confidence: 99%
“…Resistance formation of TP53 wild-type cancer cells to MDM2 inhibitors commonly results in the formation of TP53 mutations as resistance mechanism [2][3][4][5][6][7][8]. TP53 mutations may be the consequence of the selection of pre-existing TP53-mutant cell subpopulations or the induction of de novo TP53 mutations [3,[5][6][7].…”
mentioning
confidence: 99%
“…Resistance formation of TP53 wild-type cancer cells to MDM2 inhibitors commonly results in the formation of TP53 mutations as resistance mechanism [2][3][4][5][6][7][8]. TP53 mutations may be the consequence of the selection of pre-existing TP53-mutant cell subpopulations or the induction of de novo TP53 mutations [3,[5][6][7]. De novo TP53 mutations may be the consequence of the selection of cells in which TP53 mutations have occurred by chance and which would have disappeared in the absence of the selection pressure induced by an MDM2 inhibitor.…”
mentioning
confidence: 99%